2022
DOI: 10.1097/qad.0000000000003185
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir diphosphate in dried blood spots predicts future viremia in persons with HIV taking antiretroviral therapy in South Africa

Abstract: Objectives:Tenofovir diphosphate (TFV-DP) in dried blood spots (DBS) is used as a biomarker of antiretroviral therapy (ART) adherence. Recent treatment studies have shown that TFV-DP predicts future viremia in persons with HIV (PWH) but there are few data from high-burden settings. We investigated whether TFV-DP in DBS predicts future viral breakthrough in South African PWH.Design:Prospective observational cohort.Methods:We enrolled 250 adults receiving tenofovir-containing regimens, currently virally suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 26 publications
4
39
0
Order By: Relevance
“…In this study, we compared EA data with TFV-DP concentrations and established that EA increases as TFV-DP concentration increases. Although we have previously shown the ability of TFV-DP in DBS to predict future viral breakthrough, 10 here, we established that EA is also highly predictive of viral 29 directly compared the predictive value of EA to efavirenz plasma concentrations and found that EA was far superior in predicting viral suppression than the short half-life drug measure. Drug concentration monitoring has not routinely been used in the setting of antiretrovirals as they have been shown to have poor predictive values.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, we compared EA data with TFV-DP concentrations and established that EA increases as TFV-DP concentration increases. Although we have previously shown the ability of TFV-DP in DBS to predict future viral breakthrough, 10 here, we established that EA is also highly predictive of viral 29 directly compared the predictive value of EA to efavirenz plasma concentrations and found that EA was far superior in predicting viral suppression than the short half-life drug measure. Drug concentration monitoring has not routinely been used in the setting of antiretrovirals as they have been shown to have poor predictive values.…”
Section: Discussionmentioning
confidence: 50%
“…White coat adherence particularly applies to blood and urine ART concentrations [ 113 ], which reflect a shorter duration of adherence (3–5 days) [ 100 , 137 , 160 ] than hair (1 month/1 cm hair [ 33 , 117 , 138 ]). Tenofovir, emtricitabine and tenofovir diphosphate in dried blood spots are growing in popularity to measure adherence, but the costs and turnaround time for results still prohibit scale‐up [ 162 ]. Point‐of‐care assays for urine tenofovir are affordable and could be used to support adherence discussions in real‐time, but patient acceptability is mixed [ 163 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, previous work demonstrated that less than perfect adherence was associated with elevated inflammatory markers, including interleukin-2, interleukin-6, and interleukin-10, interferon-γ, tumor necrosis factor–α, and C-reactive protein, although this finding was largely driven by those with adherence <85% [ 9 ]. Moreover, in the setting of nondetectable viremia, less than perfect adherence, as measured by tenofovir-diphosphate or emtricitabine-triphosphate concentrations in dried blood spots, was a prognosticator of viral rebound, while intermittent adherence led to drug resistance mutations [ 10 , 38 , 39 ]. Combined, these data reinforce the need for high adherence to ART in PWH, as well as to understand factors such as the reasons for cannabis use that underlie nonadherence.…”
Section: Discussionmentioning
confidence: 99%